Acute Genetic Damage Induced by Ethanol and Corticosterone Seems to Modulate Hippocampal Astrocyte Signaling - Ana Laura Reyes-Ábalos; Magdalena Álvarez-Zabaleta; Silvia Olivera-Bravo; María Vittoria Di Tomaso (International Journal of Cell Biology)
Astrocytes maintain CNS homeostasis but also critically contribute to neurological and psychiatric disorders. Such functional diversity implies an extensive signaling repertoire including extracellular vesicles (EVs) and nanotubes (NTs) that could be involved in protection or damage, as widely shown in various experimental paradigms. However, there is no information associating primary damage to the astrocyte genome, the DNA damage response (DDR), and the EV and NT repertoire. Furthermore, similar studies were not performed on hippocampal astrocytes despite their involvement in memory and learning processes, as well as in the development and maintenance of alcohol addiction. By exposing murine hippocampal astrocytes to 400 mM ethanol (EtOH) and/or 1 μM corticosterone (CTS) for 1 h, we tested whether the induced DNA damage and DDR could elicit significant changes in NTs and surface-attached EVs. Genetic damage and initial DDR were assessed by immunolabeling against the phosphorylated histone variant H2AX (γH2AX), DDR-dependent apoptosis by BAX immunoreactivity, and astrocyte activation by the glial acidic fibrillary protein (GFAP) and phalloidin staining. Surface-attached EVs and NTs were examined via scanning electron microscopy, and labeled proteins were analyzed via confocal microscopy. Relative to controls, astrocytes exposed to EtOH, CTS, or EtOH+CTS showed significant increases in nuclear γlH2AX foci, nuclear and cytoplasmic BAX signals, and EV frequency at the expense of the NT amount, mainly upon EtOH, without detectable signs of morphological reactivity. Furthermore, the largest and most complex EVs originated only in DNA-damaged astrocytes. Obtained results revealed that astrocytes exposed to acute EtOH and/or CTS preserved their typical morphology but presented severe DNA damage, triggered canonical DDR pathways, and early changes in the cell signaling mediated by EVs and NTs. Further deepening of this initial morphological and quantitative analysis is necessary to identify the mechanistic links between genetic damage, DDR, cell-cell communication, and their possible impact on hippocampal neural cells.